2017
DOI: 10.1016/j.ypmed.2017.06.029
|View full text |Cite
|
Sign up to set email alerts
|

Electronic cigarette use as an aid to quit smoking in the representative Italian population PASSI survey

Abstract: This study explored electronic cigarette (e-cigarette) use as an aid to quit smoking and compared abstinence rates for different quitting methods in a representative sample of the Italian population. In the 2014–2015 PASSI survey, the ongoing Italian behavioural risk factor surveillance system, 6112 adults who smoked and made at least one quit attempt in the previous 12 months, were categorized into three groups according to the method used in their most recent quit attempt: e-cigarette only, no aid, other qui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 25 publications
1
14
0
3
Order By: Relevance
“…Questions on electronic cigarettes were not included in the 2010 GYTS, because electronic cigarettes became widespread in Italy since 2012. [9] Questions on ever electronic cigarette use specifying nicotine levels (tried electronic cigarettes with nicotine; with and without nicotine; without nicotine; don't know); on the number of days of current electronic cigarette users in the last month; on youth access to electronic cigarettes were in the 2018 GYTS only, given that electronic cigarette use among adolescents was at the beginning in Italy in the 2014 survey. Parental smoking status was used as a socioeconomic status (SES) indicator.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Questions on electronic cigarettes were not included in the 2010 GYTS, because electronic cigarettes became widespread in Italy since 2012. [9] Questions on ever electronic cigarette use specifying nicotine levels (tried electronic cigarettes with nicotine; with and without nicotine; without nicotine; don't know); on the number of days of current electronic cigarette users in the last month; on youth access to electronic cigarettes were in the 2018 GYTS only, given that electronic cigarette use among adolescents was at the beginning in Italy in the 2014 survey. Parental smoking status was used as a socioeconomic status (SES) indicator.…”
Section: Methodsmentioning
confidence: 99%
“…[6] In Italy tobacco smoking among adolescents is still high and stalling in last decades (37% in [15][16] year old students; 23% in students aged 13-15 years in 2014-2015) [4]. Moreover, Italy has a regulatory environment on electronic cigarettes quite different from other countries [9,10]: up to 2014, electronic cigarettes were and are still sold as consumer products, no rules on their use in smoke-free public areas were implemented; advertising was allowed. Then a ban in schools, and a sale ban to minors were introduced in 2013, [11] and the 2016 EU Tobacco Products Directive (TPD) with its transposition into Italy, introduced advertising ban on electronic cigarettes and other measures designed to prevent smoking initiation and electronic cigarette use among adolescents, and to restrict youth access to and availability of cigarettes and electronic cigarettes: introducing J o u r n a l P r e -p r o o f larger and mandatory pictorial health warnings covering 65% of cigarette packaging; a ban on characterising flavours including colourings, caffeine and taurine; a ban on selling cigarette packs with <20 cigarettes and roll-your own tobacco packs <30 grams.…”
Section: J O U R N a L P R E -P R O O F Introductionmentioning
confidence: 99%
“…Indeed, the safety of e-cigarette use, particularly its long-term effects, remains unclear9 10: while these e-cigarettes emit less toxicants and carcinogens than conventional cigarettes, they are still measurable and vary widely with individual puffing topography and puff duration,11 and from study to study 12 13. Although some studies showed that e-cigarettes may help smokers cut down or stop smoking conventional cigarettes,14–16 others found e-cigarettes even stop cessation or give low cessation rates, similar to those of smokers who have tried to quit with no aid 10 17–19. There is also concern that e-cigarettes may undermine efforts to ‘denormalise’ smoking 20.…”
Section: Introductionmentioning
confidence: 99%
“…27 A recent Italian national study indicated that smokers who used e-cigarettes as an aid to quit smoking had similar abstinence rates (8%) as those using no aid (9%), compared with significantly higher abstinence by those using official quitting methods (15%). Use of e-cigarettes may have been a key motivator for a number of the 8% to quit; 28 however, this cannot be proven from such a cross-sectional study alone. This concurs with other recent reviews that concluded that the evidence to date in support of the effectiveness of e-cigarettes in helping smokers quit was inconclusive.…”
Section: E-cigarettes and Cigarette Consumptionmentioning
confidence: 98%